friends please answer this question please
Attachments:
![](https://hi-static.z-dn.net/files/d36/37232c03b6630627ecf51d5a7374cf21.jpg)
Answers
Answered by
2
Answer:
17
Step-by-step explanation:
m= 3
n= 2
(m^n ) ²- (n^m) ² = ( 3²) ² - (2³) ²
= (3) ⁴- (2)^6
= 81-64
= 17
hope it helps! mark me the brain, also follow me!!
Answered by
1
(m^n)² -(n^m)²= (3²)² -(2³)²
=(3)4 -(2)6
= 81-64=17
Similar questions
History,
3 months ago
English,
3 months ago
Chemistry,
3 months ago
Science,
7 months ago
Computer Science,
7 months ago